A novel GPR119 agonist DA-1241 preserves pancreatic function via the suppression of ER stress and increased PDX1 expression - Mi-Kyung Kim, Ph.D (Elsevier, 2021)
DA-1241 is a novel small molecule G protein-coupled receptor 119 (GPR119) agonist in early clinical development for type 2 diabetic patients. This study aimed to elucidate the pharmacological characteristics of DA-1241 for its hypoglycemic action. DA-1241 potently and selectively activated GPR119 with enhanced maximum efficacy. DA-1241 increased intracellular cAMP in HIT-T15 insulinoma cells (EC50, 14.7 nM) and increased insulin secretion (EC50, 22.3 nM) in association with enhanced human insulin promoter activity. Accordingly, postprandial plasma insulin levels were increased in mice after single oral administration of DA-1241. Postprandial glucose excursion was significantly reduced by single oral administration of DA-1241 in wild-type mice but not in GPR119 knockout mice. GLP-1 secretion was increased by DA-1241 treatment in mice. Thus, upon combined sitagliptin and DA-1241 treatment in high-fat diet/streptozotocin (HFD/STZ)-induced diabetic mice, plasma active GLP-1 levels were synergistically increased. Accordingly, blood glucose and triglyceride levels were significantly lowered both by DA-1241 and sitagliptin alone and in combination. Immunohistochemical analysis revealed that β-cell mass with reduced PDX1 levels in the islets from HFD/STZ diabetic mice was significantly preserved by DA-1241, whereas increased glucagon and BiP levels were significantly suppressed. In HIT-T15 insulinoma cells subjected to ER stress, decreased cell viability was significantly rescued by treatment with DA-1241. Additionally, increased apoptosis was largely attenuated by DA-1241 by inhibiting BiP and CHOP expression through suppression of p38 MAPK. In conclusion, these studies provide evidence that DA-1241 can be a promising antidiabetic drug by potentially preserving pancreatic functions through suppressing ER stress and increasing PDX1 expression.